2003
DOI: 10.1111/j.1939-1668.2003.tb00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Educators and Practice: How to Stay Current

Abstract: Interior design educators must stay informed about new developments in design practice. Although informal visits to design firms are important, the quality of information gained could be improved through more formal and structured visits. The goal of this project was to develop a method for interior design educators to systematically collect information about current design practice while observing activities, processes, and service outcomes in design firms to inform their knowledge of entry‐level practice. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Over the past 40 years, several studies have identified competencies needed for entry-level interior designers (Hernecheck, Rettig, & Sherman, 1983;Hoffman, 1983;Myers, 1982) and professional practice activities (Benhamou, 1980). Later studies focus on communication, business skills (Tew, 1992) and occupational expectations (Lee & Hagerty, 1996); followed by studies citing the importance of an ongoing connection between practice and education (Black, 2000;Blossom et al, 2002;Watson et al, 2003) and annual rankings of universities with the most-prepared students (Design-Intelligence [DI], 2012[DI], , 2013[DI], , 2014[DI], , 2015[DI], , 2016 and most recently factors influencing the motivations of internship providers (Fishburne, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 40 years, several studies have identified competencies needed for entry-level interior designers (Hernecheck, Rettig, & Sherman, 1983;Hoffman, 1983;Myers, 1982) and professional practice activities (Benhamou, 1980). Later studies focus on communication, business skills (Tew, 1992) and occupational expectations (Lee & Hagerty, 1996); followed by studies citing the importance of an ongoing connection between practice and education (Black, 2000;Blossom et al, 2002;Watson et al, 2003) and annual rankings of universities with the most-prepared students (Design-Intelligence [DI], 2012[DI], , 2013[DI], , 2014[DI], , 2015[DI], , 2016 and most recently factors influencing the motivations of internship providers (Fishburne, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Academic programs can also use internships within the curriculum to supplement student-learning outcomes (Black, 2000), which can contribute to addressing the Council of Interior Design Accreditation (CIDA) standards in addition to other broader university accreditation standards. Additionally, knowing what students are doing in the field assists faculty in staying current with practice (Watson, Guerin, & Ginthner, 2003), which allows for course updating and curriculum revisions.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few decades, the characteristics, attributes, knowledge, and skills expected from entry-level interior designers in the United States has been well documented in seven studies (Baker & Sondhi, 1989;Douthitt & Hasell, 1985;Hoffman, 1983;Hernecheck et al, 1983;Myers, 1982;Scarton, 2012;Tarver, 2013) and professional practice activities (Benhamou, 1980). Later studies focused on communication, business skills (Tew, 1992) and occupational expectations (Lee & Hagerty, 1996); followed by studies citing the importance of an ongoing connection between practice and education (Black, 2000;Blossom et al, 2002;Watson et al, 2003) followed by research citing the importance of hard and soft skills needed for hiring emerging interior design professionals (Gale et al, 2017).…”
Section: Interior Design Competenciesmentioning
confidence: 99%
“…Other research also attests to the importance of understanding the business aspect of interior design. For example, Watson, Guerin, and Ginthner generated The Design Practice Update Manual instrument specifically to support academics understanding of current design practice issues and trends explaining, “it is essential for interior design educators to immerse themselves in design practice in a structured way, enabling them to update their knowledge of design practice” (Watson, Guerin, & Ginthner, , p. 102). Finally, the inclusion of “professional practice” as one of the six core categories in the interior design body of knowledge defined by Guerin and Martin () further speaks to the importance of business‐related issues in interior design education and research.
The purpose of the study presented here was to assess the degree of burnout among practicing interior designers while also identifying which, if any, individual or situational factors could be contributing or associated with reported burnout levels .
…”
Section: Purposementioning
confidence: 99%